Student’s Perception of Using Zoom Meeting Application in The English Learning Process at The Second Grade of SMK Kesehatan Prima Nusantara in The Academic Year 2021/2022 - Hariri, Badria; Reflinda, Reflinda (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aimed to determine the perception of using Zoom Meeting Applications as an application for learning English for students. The use of Zoom Meeting Applications in learning English had been used by English teacher. The kind of this research was a survey through a quantitative method. The population was the second grade of SMK Kesehatan Prima Nusantara in the Academic Year 2021/2022. The researcher used the total sampling technique because the population was less than 100 students. The instrument of this research was a questionnaire that consisted of 45 items.The total percentage of data analysis was the highest category that was chosen was disadvantages of Zoom Meeting Application (70%), during zoom advantages (68%), advantages of Zoom Meeting Application (64%), and the lowest chosen category are features of Zoom Meeting Application (62%). The result of students’ perception of using Zoom Meeting Application in English learning was 66%. The researcher concluded that students’ perception is enough perception by finding the average of each process chosen by the students. Thus, the result of the research showed that the students dominantly neutral the use of Zoom Meeting Application in English learning.